Which pair shows equivalent expressions? 2 x + 10 = negative 2 (x minus 5) Negative 2 (x + 5) = 2 x minus 10 Negative 2 x minus 10 = negative 2 (x + 5) Negative 2 (x minus 5) = negative 2 x minus 10

Respuesta :

Answer:

C. –2x – 10 = –2(x + 5)

Step-by-step explanation:

Clearer choices:

2x + 10 = –2(x – 5)

–2(x + 5) = 2x – 10

–2x – 10 = –2(x + 5)

–2(x – 5) = –2x – 10

All choices have either:

–2(x – 5) for A and D

or –2(x + 5) for B and C

Simplify these expressions by expanding with the distributive property. Multiply the outside term "–2" with each term inside the brackets.

–2(x – 5)

= (–2*x) – (–2*5)          Multiply each term by the coefficient

= –2x – (–10)           Simplify the double negative to a positive

= –2x + 10             Expanded expression

This is not the same answer in A and D. They are not correct.

–2(x + 5)

= (–2*x) + (–2*5)           Multiply each term by the coefficient

= –2x + (–10)          Adding a negative is the same as subtraction

= –2x – 10             Expanded expression

This is the same answer for option C.

Therefore "C" is the answer.

Answer:

C

Step-by-step explanation:

I just took the test